Sosialisasi Implementasi Media Layanan Informasi dengan Tema Kesejahteraan Psikologis - Shinta Mayasari; Ranni Rahmayanthi; Eka Kurniawati; Redi eka Andriyanto (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2022)
Health is a basic need for every individual. Health is not only related to physical health, but also mental health. Psychological wellbeing is a manifestation of an individual's mental health. Psychological wellbeing is positively correlated with social support, internal locus of control, optimism, job satisfaction, self-efficacy, contextual performance, gratitude, resilience, and job involvement. Individual processes to achieve psychological wellbeing need to be pursued through the provision of systematic guidance services. Information service is one of the important services to be implemented because every individual is basically thirsty for information. Information can be used by individuals to increase their knowledge and understanding of the concept of psychological wellbeing. This community service is designed to implement psychological wellbeing information services with educational comic media. Educational comics media are considered to be more effective in delivering information, more varied so that they do not become saturated, and can be accessed wherever they are.